2004
DOI: 10.1523/jneurosci.5039-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inCaenorhabditis elegansCytoplasmic Dynein Components Reveal Specificity of Neuronal Retrograde Cargo

Abstract: We describe Caenorhabditis elegans dynein complex mutants, which misaccumulate synaptic proteins at the ends of neuronal processes. Ultrastructural analysis revealed irregularly sized vesicles that likely represent accumulation of cargo. We propose that synaptobrevin, synaptotagmin, and UNC-104 are specific cargoes of the dynein complex. Many cargoes link to dynein via interactions between dynactin and vesicle-associated spectrin. However, loss of spectrin results in only mild and occasional defects in synapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
113
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 67 publications
(102 reference statements)
17
113
0
1
Order By: Relevance
“…For example, either EHNA or vanadate, which both inhibit dynein and other enzymes, inhibits axonal transport (Ekstrom and Kanje, 1984;Wang et al, 1995;Lalli et al, 2003). More specific dynein inhibition by genetic mutation causes changes in axonal organelle distributions consistent with transport defects (Bowman et al, 1999;Martin et al, 1999a;Koushika et al, 2004). The live analysis here shows that dynein mutations inhibit specific retrograde run parameters and flux but that they leave anterograde transport largely unchanged.…”
Section: Motors For Axonal Transport Of Mitochondriamentioning
confidence: 66%
“…For example, either EHNA or vanadate, which both inhibit dynein and other enzymes, inhibits axonal transport (Ekstrom and Kanje, 1984;Wang et al, 1995;Lalli et al, 2003). More specific dynein inhibition by genetic mutation causes changes in axonal organelle distributions consistent with transport defects (Bowman et al, 1999;Martin et al, 1999a;Koushika et al, 2004). The live analysis here shows that dynein mutations inhibit specific retrograde run parameters and flux but that they leave anterograde transport largely unchanged.…”
Section: Motors For Axonal Transport Of Mitochondriamentioning
confidence: 66%
“…Palmer et al [14] reported that depleting DLIC1 by RNAi in HeLa cells disrupted the Golgi apparatus, but Sivaram et al [11] claimed that it had no effect on the Golgi. Mutating Dlic gene blocks the transport of neuronal retrograde cargoes in worms and flies [16][17][18] and results in dendritic and axonal defects in neurons, such as a reduction in the length and number of dendrite branches in Drosophila. However, mice with a point mutation Dlic1 N235Y display an increase in dendrite length of cortical neurons (with no changes in branching) and the number of dendrite branches of dorsal root ganglia (DRG) neurons, in addition to its increased anxiety-like behavior and altered gait [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our time-lapse imaging experiments showed that DLK-1(K162A) puncta moved both anterogradely and retrogradely (Fig. 4D) and that the retrograde DLK-1 movements were abolished by a temperature-sensitive mutation in dhc-1, the cytoplasmic dynein heavy chain (33)(34)(35) (Fig. 4D).…”
Section: Dlk-1 Retrograde Signaling Contributes To Plm Branch Defectsmentioning
confidence: 92%